OP0159 Complement Factors in Osteoarthritis Articular Compartments. (9th June 2015) - Assirelli, E.; Dolzani, P.; Pulsatelli, L.; Addimanda, O.; Meliconi, R.
Abstract : Background: Osteoarthritis (OA) is characterized by the degradation and breakdown of cartilage and by chronic, low-grade inflammation. Even though multiple factors are probably active in this process, recent evidence has implicated the innate immune system as being principally responsible and, in particular, the roles of synovial macrophages and the complement system. Furthermore, a recent study has identified a central role for the activation of the complement system in the pathogenesis of OA, finding an abnormally high expression and activation of complement in human osteoarthritic joints and the specific contribution of complement components 5 and 6 (C5, C6) and of the membrane attack complex (MAC) (1). The complement system consists of several proteins which contribute to an enzymatic cascade ending in lysis. Two main, different pathways converge into C3 factor activation. In the classical pathway C4 is involved, while in alternative pathway Factor-b is involved. Objectives: The aim of this study was to investigate complement involvement in OA articular tissues (cartilage and synovium), focusing in particular on the expression of factors involved in the classical or alternative pathway: complement component 3 (C3), C4 and complement factor-b. Methods: Chondrocytes, cartilage biopsies and synoviocytes were obtained from OA patients undergoing joint replacement surgery. Chondrocyte high density, synoviocytes and cartilage biopsy cultures were set up with or without pro-inflammatory (IL-1β) stimulus. RNA was extracted from chondrocyte cultures, cartilage biopsies and synoviocytes and real time PCR analyses of factor-b, C3 and C4 genes were performed. Culture supernatants were analysed for C5b-9 complex production using enzyme-linked immuno-sorbent assay (ELISA). Results: All complement factors analyzed were expressed both in OA chondrocytes and in OA synoviocytes. Regarding the chondrocytes (high density culture and cartilage explants n=11), factor-b gene expression was significantly higher than C3 and C4 (Wilcoxon matched pairs test p=0.0046 and p=0.0010, respectively). No difference between C3 and C4 expression was found. Furthermore, factor-b and C3, but not C4 gene expression was significantly induced by IL-1β stimulation (p=0.0425 and p=0.0010, respectively). In cultured synoviocytes (n=6), also, Factor-b and C3, but not C4, were significantly induced by IL-1β stimulation (p=0.056 and p=0.0313, respectively). Preliminary data on C5b-9 ELISA quantification showed no presence of the protein in synoviocyte culture supernatants. On the other hand, a large amount of this complex was detected in the supernatants of OA cartilage biopsies. Conclusions: Complement factors are expressed by OA articular tissues and their expression is further increased by inflammatory stimulus. Moreover, the enhanced basal production of factor-b and the different modulation by IL-1β of the production of the complement factors suggests a major involvement of the alternative pathway of complement activation. References: Wang Q. et al, Identification of a central role for complement in osteoarthritis, nature medicine 2011 Disclosure of Interest: None declared